6(k-7)-(8+9k)=-4k

Simple and best practice solution for 6(k-7)-(8+9k)=-4k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(k-7)-(8+9k)=-4k equation:


Simplifying
6(k + -7) + -1(8 + 9k) = -4k

Reorder the terms:
6(-7 + k) + -1(8 + 9k) = -4k
(-7 * 6 + k * 6) + -1(8 + 9k) = -4k
(-42 + 6k) + -1(8 + 9k) = -4k
-42 + 6k + (8 * -1 + 9k * -1) = -4k
-42 + 6k + (-8 + -9k) = -4k

Reorder the terms:
-42 + -8 + 6k + -9k = -4k

Combine like terms: -42 + -8 = -50
-50 + 6k + -9k = -4k

Combine like terms: 6k + -9k = -3k
-50 + -3k = -4k

Solving
-50 + -3k = -4k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '4k' to each side of the equation.
-50 + -3k + 4k = -4k + 4k

Combine like terms: -3k + 4k = 1k
-50 + 1k = -4k + 4k

Combine like terms: -4k + 4k = 0
-50 + 1k = 0

Add '50' to each side of the equation.
-50 + 50 + 1k = 0 + 50

Combine like terms: -50 + 50 = 0
0 + 1k = 0 + 50
1k = 0 + 50

Combine like terms: 0 + 50 = 50
1k = 50

Divide each side by '1'.
k = 50

Simplifying
k = 50

See similar equations:

| 8n-3(5)= | | x^2+4x=5x | | -2x+21=7x-15 | | 8(2x-4)+5(3x+6)=29 | | (2x+28)(4x+10)= | | -3x+1=-2(3x+10) | | 2w^2+2w=34 | | 5r+15=2.25r | | 3(6+x)=30 | | 3x+4-2-x=14 | | -3(e+4)=4w-5 | | -3+2x=-x-6 | | 1-6x=5-4x | | 22-44= | | 13x+9=-15 | | 2a+4.2=3a-16 | | 2y+4=26 | | XY=98 | | 12p=-4 | | -6n+7n+4= | | 5k+8(k-4)=-84 | | 4x-7=x-34 | | 5y-5=7y+9+10y+4 | | -11=1+8k | | k*(-9k)*k=0 | | X(3x-5)=(3x+8)(x-5) | | 3+2(3n+2)=41 | | 11x+13(19-x)=211 | | -9t(t-2)=4(t-15) | | 2y+120=180 | | 4b=120-5t | | 2b+5=b+10 |

Equations solver categories